Potensi Antibakteri Ekstrak Etanol Batang Balakka (Phyllanthus emblica L.) terhadap Staphylococcus epidermidis serta Evaluasi Mutu Fisik Krim - Nabila Nasuha; Muharni Saputri; Ika Julianti Tambunan; Siti Muliani Julianty; Ulva Wirdana Br Sitepu; Nabila Syahputri; Manuella Sinaga; Devi Yanti Syahputri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Balakka (Phyllanthus emblica L) is a wild plant, commonly used as a cooking spice called holat. The stem of balakka is believed to contain alkaloids, flavonoids, and tannins that have antibacterial properties. Most previous studies have focused on the fruit and leaves of balakka. On the other hand, Staphylococcus epidermidis bacteria are normal flora on human skin that cause infections. The increasing resistance of these bacteria to antibiotics makes it important to find alternative natural antibacterial agents. The purpose of this study was to examine the antibacterial activity of balakka stem extract and cream against Staphylococcus epidermidis bacteria and to evaluate the physical quality of the cream. This study used experimental methodology. The maceration method used ethanol p.a. on 100 g of balakka stem simplisia. The stages included phytochemical screening, cream formulation with concentrations of 1%, 2%, and 3%, and physical quality tests (organoleptic, homogeneity, emulsion type, pH, viscosity, stability, and irritation). Antibacterial tests were carried out using the agar well diffusion method on extracts and cream preparations. The results showed that 19.30 g of thick extract was obtained, which was positive for alkaloids, flavonoids, and tannins. The resulting cream met physical quality standards, was homogeneous, had an oil-in-water (O/W) emulsion type, a pH of 5.3–6.2, was stable, and did not cause irritation. The antibacterial activity of the extract showed inhibition zones of 14.5 mm (100 mg/ml), 11.5 mm (75 mg/ml), and 8.5 mm (50 mg/ml), while the cream showed 5.5 mm (1%), 7.5 mm (2%), and 9.5 mm (3%). Thus, ethanol extract of balakka stems has potential as an antibacterial agent and can be formulated into a safe cream that meets physical quality standards.